Semi-physical Verification Technology for Dynamic Performance of Internet of Things System - Yu, Xiaolei; Wang, Donghua; Zhao, Zhimin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book combines semi-physical simulation technology with an Internet of Things (IOT) application system based on novel mathematical methods such as the Fisher matrix, artificial neural networks, thermodynamic analysis, support vector machines, and image processing algorithms. The dynamic testing and semi-physical verification of the theory and application were conducted for typical IOT systems such as RFID systems, Internet of Vehicles systems, and two-dimensional barcode recognition systems. The findings presented are of great scientific significance and have wide application potential for solving bottlenecks in the development of RFID technology and IOT engineering. The book is a valuable resource for postgraduate students in fields such as computer science and technology, control science and engineering, and information science. Moreover, it is a useful reference resource for researchers in IOT and RFID-related industries, logistics practitioners, and system integrators.
Research progress of semi-physical verification technology based on photoelectric sensing -- Multi-antenna optimal receiving theory and semi-physical verification of RFID-MIMO system -- Thermodynamic analysis and semi-physical verification of the effect of temperature on dynamic performance of RFID -- Adaptive analysis and semi - physical verification of RFID multi-tag geometric distribution based on Fisher matrix -- Application of artificial neural network in RFID multi-tag distribution optimization and semi - physical verification -- Optimal distribution and semi-physical verification of RFID multi-tag based on image processing -- Application of semi-physical verification technology in other fields of internet of things.
Keywords: Telecommunication; Multibody systems; Vibration; Mechanics, Applied; Electronics; Communications Engineering, Networks; Multibody Systems and Mechanical Vibrations; Microwaves, RF Engineering and Optical Communications; Electronics and Microelectronics, Instrumentation